GPU Accelerated Multiple-Relaxation-Time Lattice Boltzmann Simulation of Convective Flows in a Porous Media - Molla, Md Mamun; Haque, Md Jahidul; Khan, Md Amirul Islam; Saha, Suvash C. (Frontiers in Mechanical Engineering, 2018)
A two-dimensional (2D) multiple-relaxation-time (MRT) lattice Boltzmann method (LBM) is used for porous media with the Brinkman-Forchheimer extended Darcy model to investigate the natural and mixed convection flows in a square cavity. This Brinkman-Forchheimer model is directly used through the forcing moments as source term. A Tesla K40 NVIDIA graphics card has been used for the present Graphics Process Unit (GPU) parallel computing via Compute Unified Device Architecture (CUDA) C platform. The numerical results are presented in terms of the velocity, temperature, streamlines, isotherms and local and average Nusselt numbers. For the wide range of Rayleigh numbers, $(Ra = 10^3$ to $10^{10}$), Reynolds numbers, Darcy numbers and the porosities, the average Nusselt number is compared with the available results computed by finite element method (FEM) and single-relaxation-time (SRT) lattice Boltzmann method and the agreement shows quite well. {\blue{The results are also validated with the previous experimental results.}} The simulations speed up maximum 144x using CUDA C in GPU comparing with the time of FORTRAN 90 code using a single core CPU simulation.